2020
DOI: 10.1021/acsmaterialslett.0c00033
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Emission Enhancements of Mn2+-Doped Cesium Lead Chloride Perovskite Nanocrystals

Abstract: Metal-halide perovskites (MHPs) have attracted tremendous attention because of their excellent performance in photovoltaic devices, such as solar cells. However, because of the crucial relationship between emission intensity and performance, pressure-quenching of optical emission greatly restrict the potential application of MHPs. Here, we reported the unique pressure-induced emission enhancement (PIEE) of CsPb x Mn 1−x Cl 3 NCs. Different from other PIEE phenomena, the PIEE of CsPb x Mn 1−x Cl 3 NCs was cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…In some cases, an aromatic ring is attached to a short alkyl chain, which leads to slight changes in color coordinates and distance between Pb–Br slabs ( d ‐spacing). [ 12,30,35 ] Type III organoamines have been rarely studied in 2D layered perovskites, [ 36 ] however, they have been used to produce efficient and thermally stable solar cells when combined with 3D perovskites [ 37 ] and to fabricate bright light‐emitting nanocubes. [ 38 ] The next question we formulate for this type of molecules is the role of the aliphatic chain length (see Figure 1b) concerning the robustness and light emission of the resulting RPLP.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, an aromatic ring is attached to a short alkyl chain, which leads to slight changes in color coordinates and distance between Pb–Br slabs ( d ‐spacing). [ 12,30,35 ] Type III organoamines have been rarely studied in 2D layered perovskites, [ 36 ] however, they have been used to produce efficient and thermally stable solar cells when combined with 3D perovskites [ 37 ] and to fabricate bright light‐emitting nanocubes. [ 38 ] The next question we formulate for this type of molecules is the role of the aliphatic chain length (see Figure 1b) concerning the robustness and light emission of the resulting RPLP.…”
Section: Resultsmentioning
confidence: 99%
“…observed the unique pressure‐induced emission enhancement (PIEE) in Mn 2+ ‐doped CsPbCl 3 NCs. [ 151 ] The PIEE of CsPb x Mn 1– x Cl 3 NCs was caused by improved energy release from Mn 2+ d–d orbital transition due to the pressure‐induced isostructural phase transition (Figure 8d,e). The PL still exists when the pressure is up to 20 GPa, and such high pressure makes them exhibit remarkable applications in pressure sensors, pressure switches, and anti‐counterfeiting labels.…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 99%
“…d,e) PL spectra of CsPb x Mn 1– x Cl 3 NCs under the different pressures. [ 151 ] The inset of panel (e) is the PL spectrum of CsPbCl 3 NCs at 1 atm. The right panels show the optical microscopic images of CsPb x Mn 1– x Cl 3 NCs at different pressures.…”
Section: Mn2+‐doped Luminescent Halide Perovskites With Different Strmentioning
confidence: 99%
“…reported the unique pressure‐induced emission enhancement of CsPb x Mn 1− x Cl 3 NCs. [ 28 ] Furthermore, Zhang et al. reported that thermally annealed Mn 2+ :CsPbCl 3 NCs gained higher electrical conductivity and improved photoelectric response compared to the ambient state before compression.…”
Section: Introductionmentioning
confidence: 99%